Spanish contemporary poetry : An anthology - Cullell, Diana (Book collections on Project MUSE., 2014)
This book presents a selection of Spanish peninsular poetry from the 1970s to the present day, with an introductory study of the most relevant poetic trends and poetic groups of the period, followed by guided and close readings of each poem. The anthology includes poems by twenty-two authors selected according to their literary rigour and with attention to the relevance of their work, a comprehensive introductory study, notes, thorough individual commentaries to the poems, and lists of selected vocabulary and rhetorical terms that provide accessibility to the anthology. The poetic selection is divided into sections and subsections in order to aid its pedagogical intent, covering: the poetry written during the transition to democracy; the emergence of poetry written by women in the 1980s; the Spanish poetic field of the 1990s; the poetry written at the turn of the new millennium; and some of the youngest voices in Spanish poetry today. English-speaking students working in the field of Hispanic literature, but also a more general reader keen on literature written in Spanish language, should thoroughly enjoy this work.